2008
DOI: 10.1242/dev.021519
|View full text |Cite
|
Sign up to set email alerts
|

Distinct sequential cell behaviours direct primitive endoderm formation in the mouse blastocyst

Abstract: The first two lineages to differentiate from a pluripotent cell population during mammalian development are the extraembryonic trophectoderm (TE) and the primitive endoderm (PrE). Whereas the mechanisms of TE specification have been extensively studied, segregation of PrE and the pluripotent epiblast (EPI) has received comparatively little attention. A current model of PrE specification suggests PrE precursors exhibit an apparently random distribution within the inner cell mass of the early blastocyst and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
804
2
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(877 citation statements)
references
References 28 publications
61
804
2
10
Order By: Relevance
“…Genetic manipulations in ESCs suggested that the two transcription factors Nanog and Gata6 may act in a mutually antagonistic manner to determine the two lineages. In the embryo, however, Nanog and Gata6 both begin to be expressed in an apparently stochastic manner at around the eight-cell stage (Dietrich and Hiiragi 2007), and they can be colocalized in some cells of the ICM at least until the 32-cell stage (Plusa et al 2008). Hypoblast markers, such as platelet-derived growth factor receptor a (PDGFRa) and Sox17, also initially show heterogeneous expression in the early blastocyst.…”
Section: Formation Of the Blastocystmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic manipulations in ESCs suggested that the two transcription factors Nanog and Gata6 may act in a mutually antagonistic manner to determine the two lineages. In the embryo, however, Nanog and Gata6 both begin to be expressed in an apparently stochastic manner at around the eight-cell stage (Dietrich and Hiiragi 2007), and they can be colocalized in some cells of the ICM at least until the 32-cell stage (Plusa et al 2008). Hypoblast markers, such as platelet-derived growth factor receptor a (PDGFRa) and Sox17, also initially show heterogeneous expression in the early blastocyst.…”
Section: Formation Of the Blastocystmentioning
confidence: 99%
“…Nanog protein is initially found at varying levels throughout the ICM (Dietrich and Hiiragi 2007;Plusa et al 2008). By the late blastocyst stage, however, Nanog is precisely restricted to the new-formed epiblast, where it is present at similar levels in all cells.…”
Section: Formation Of the Blastocystmentioning
confidence: 99%
“…B 369: 20130549 mutually exclusive expression of these two transcription factors [40,41]. These cells then physically sort based on a variety of cell behaviours, including differential adhesion, apoptosis and downregulation of the PE programme in inside cells [41], resulting in the segregation of Epi and PE layers by E4.5. In addition to Nanog, a number of other Epi markers such as Rex1 [42] are expressed in early blastomeres and are later restricted to the pluripotent Epi.…”
Section: Gene Regulatory Network and Totipotencymentioning
confidence: 99%
“…The expression of these canonical lineage markers begins with OCT4, GATA6, NANOG and CDX2, all apparent by the 8-cell stage [38,41]. Many of these transcription factors continue to be coexpressed into blastocyst stages ( figure 1a).…”
Section: Gene Regulatory Network and Totipotencymentioning
confidence: 99%
“…First, they support the notion that the divergence of TE and PrE involves reciprocal genetic changes within GRNs shared, at least in part, with the ICM and Epi. These changes ultimately derive from dynamic and reinforcing cellular interactions, in which cell polarity and positional cues appear to trigger events separating TE from ICM, while cell division orientation, migration and apoptosis drive the divergence of PrE and Epi [114][115][116]. Secondly, these studies provide evidence that pluripotency factors function in networks regulating lineage-specific differentiation in the embryo.…”
Section: (B) Regulatory Network Governing the First Cell Fate Choicesmentioning
confidence: 84%